Analisis Framing Berita "Gempur Rokok Ilegal" dalam Perspektif Komunikasi Pemerintah Daerah: : Studi Kasus Website Mojokertokab.Go.Id - Friska Septin Arianti Putri; Rahmad Saiful Ramadhani; Masnia Ningsih (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The increasing accessibility of information in the digital era has accelerated the dissemination of messages. In the context of the rampant circulation of illegal cigarettes in society, the Mojokerto Regency Government is striving to address this issue by launching the “Crackdown on Illegal Cigarettes” campaign. The aim of this study is to clarify the message framework used to understand how news about “Crackdown on Illegal Cigarettes” is reported on the mojokertokab.go.id website. This research is a qualitative descriptive study utilizing Robert N. Entman’s framing analysis model, which includes: identifying the problem, diagnosing its causes, assessing the moral implications, and proposing solutions. Data collection methods include documentation and literature review, with the object of the study being news coverage related to the “crackdown on smuggled cigarettes.” The findings of this study indicate that the news coverage of the “Crackdown on Illegal Cigarettes” on the mojokertokab.go.id website emphasizes the importance of supporting legal cigarettes because they contribute to public welfare through the Tobacco Excise Sharing Fund (DBHCT) program. Therefore, minimizing the circulation and sale of illegal tobacco is crucial to ensure that DBHCT can be utilized optimally, thereby enhancing overall community welfare.